MERTK missense variants in three patients with retinitis pigmentosa. (2nd January 2023) - Poli, Federica E.; Yusuf, Imran H.; Clouston, Penny; Shanks, Morag; Whitfield, Jennifer; Charbel Issa, Peter; MacLaren, Robert E.
ABSTRACT: Background: MERTK (MER proto-oncogene, tyrosine kinase) is a transmembrane protein essential in regulating photoreceptor outer segment phagocytosis. Biallelic mutations in MERTK cause retinal degeneration. Here we present the retinal phenotype of three patients with missense variants in MERTK . Materials and methods: All patients underwent a full clinical examination, fundus photography, short-wavelength fundus autofluorescence and optical coherence tomography imaging. Two patients also underwent Goldmann visual field testing and electroretinography was undertaken for the third patient. Molecular genetic testing was undertaken using next generation or whole-exome sequencing with all variants confirmed by Sanger sequencing. Results: The first patient was a 29-year-old female heterozygous for a missense variant (c.1133C>T, p.Thr378 Met) and a nonsense variant (c.1744_1751delinsT, p.Ile582Ter) in MERTK . The second patient was a 26-year-old male homozygous for a c.2163T>A, p.His721Gln variant in MERTK . The third patient was an 11-year-old female heterozygous for a deletion of exons 5–19 and a missense variant (c.1866 G>C, p.Lys622Asn) in MERTK . Reduced night vision was the initial symptom in all patients. Fundoscopy revealed typical signs of retinitis pigmentosa (RP) with early-onset macular atrophy. All three MERTK missense variants affect highly conserved residues within functional domains, have low population frequencies and are predicted to be pathogenic in silico . Conclusions: We report three missense variants in MERTK and present the associated phenotypic data, which are supportive of non-syndromic RP. MERTK is a promising candidate for viral-mediated gene replacement therapy. Moreover, one variant represents a single nucleotide transition, which is theoretically targetable with CRISPR-Cas9 base-editing.